(untitled) (Global Journal of Management and Business Research, 2020)
This study evaluates the effects of the National Policy for Territorial Consolidation and Reconstruction PNCRT on security in the regions affected by the armed conflict It focused on analysing its effect on life threats infrastructure damage and the spread of illicit crops through a combination of statistical techniques called Propensity Score Matching and Difference in Differences